Customer‐Based Customization and Price Competition. (5th December 2022) - Colombo, Stefano; Garella, Paolo G.
Abstract : Among the many consequences for production processes, new technologies, including 3D‐printing and web‐based co‐design, provide end‐users with increasingly effective means to locally reshape and co‐produce products to fit their needs, decentralizing part of the production process. But do firms have an incentive to design goods that are self‐customizable or rather to retain centralized production? Is users' surplus increased when self‐customization is an available option? We analyze a duopoly where firms can offer a standard version only, or a menu with two product/price options: a standard and a customizable version. Different from firm‐based customization, customizing consumers pay the same price to the firm, who cannot price discriminate among them. We find that both firms' introducing a self‐customizable product can be an equilibrium, with an increase in profits, consumers' surplus, and welfare. However, there also arise situations in which one firm only produces standardized goods. The equilibrium configuration depends upon the cost of self‐customization and the distribution of consumers.